Materias primas alternativas para la fabricación de cementos más ecoeficientes de baja energía - Goñi, S.; Guerrero, A.; Macías, A.; Lorenzo, M.P. (Revista ALCONPAT, 2011)
The industrial and technological development poses major challenges due to the high amount ofwastes generated; a lot of research focuses on reduce environmental impact. This paperconcentrates in byproducts from the incineration of municipal solid waste (MSW) which,regardless of the incineration system, involve large amounts of fly ash and slag that can berevalued or otherwise stabilized, so to reduce their environmental impact. Among the currentactions for minimizing this waste is their use as raw materials in the manufacture of cement. Thework aims on the synthesis of an "eco-efficient cement" that incorporates fly ash fromincineration of municipal solid waste (FAIMSW) as secondary raw material. The innovativemanufacturing process represents an important contribution for the sustainable development ofthe industry, as it involves an important reduction of clinkerization temperature (< 1100°C) and aminimization of CO2 emissions.